How Startups Develop CSR to Build Brand Reputation: A Qualitative Pilot Study - Papa, Elena; Daskou, Sofia (My University, 2024)
The abstract should summarize the contents of the paper in short terms, i.e., 150–250 words. The paper investigates how southeast European startups utilize Corporate Social Responsibility (CSR) to enhance their brand. It explores factors driving the adoption of CSR practices by startups, their significance, and best practices of CSR implementation, and also addresses customers’ perceptions of startup sustainability, CSR initiatives, and the resulting impact on the firm’s reputation. To conduct this research, an interpretive study design utilizing thematic analysis was conducted. The sample included CSR specialists, advertisers, and startup owners, with the study findings reflecting the theoretical aspects of CSR. The data revealed a strong focus on the social dimension of CSR implementation, highlighting practices that prioritize human resources, the environment, and broader societal well-being. Key themes that emerged from the study include the importance of developing and implementing environmental awareness programs, engaging in volunteer work, and promoting labor-related initiatives. The results underscored the significance of ethical practices in fostering a positive work environment for employees and emphasized the pivotal role of the firm’s purpose in brand building. Establishing strong relationships with the community, both at large and within the company’s operational area, emerged as a critical factor in effectively implementing CSR for brand reputation. The reciprocal relationship between customers and the company, where customers perceive a genuine commitment to the community rather than a sole focus on profit, serves as the foundation for a sustainable business trajectory. Furthermore, voluntary actions organized by the firm to support the community were identified as instrumental in building brand reputation.
Keywords: CSR; Startup; Branding; Reputation management; Ethics; Marketing